Slope Stability Study Using Finite Element Method on the Road Construction Project Bululawang-Sidomulyo-Tambakrejo STA 14+675, Blitar Regency, East Java Province - Saiful Mahfud; Herman Wahyudi; Yudhi Lastiasih (Interdisciplinary Social Studies, 2025)
This study was conducted at STA 14+675 of the Bululawang–Sidomulyo–Tambakrejo road construction project, there was a landslide on the excavation slope with an initial geometry of 4V:1H and a height of about 10 meters. This study aims to identify the factors that cause landslides and evaluate effective treatment alternatives. The research method uses a quantitative descriptive approach supported by finite element method (FEM) based numerical analysis through PLAXIS 3D software. The soil characteristics were obtained from bore log data, soil laboratory tests, and geoelectric surveys and then compiled into a stratigraphic model for modelling. The results of the analysis showed that the increase in groundwater level had a significant effect on the reduction of slope safety factors due to increased pore pressure and decrease in effective stress of soil. The existing condition has a safety factor of 1.498 and reaches unstable conditions when the groundwater level rises to an elevation of +20.5 meters with an SF value of 0.980. Based on the results of the modelling variation slope stabilization, regrading the slope ratio to 1V:1H indicates the most stable slope condition (SF>1.5). Evaluation of slope stabilization show that regrading the first bench to 1V:1H and maintaining a steep slope 4V:1H  in the second bench provides the most cost-effectives solution with unit cost IDR 35,685,000.00 m3/m and safety factor of 1,512. However, regrading both the first and second benches to 1V:1H resulted in a higher SF value of 1.782 but required approximately 15% more land compared previous modelling variation The most stable slope stabilization conditions was obtained by regrading the first bench to 1V:1H combined with a soil retaining wall structure on the second bench resulted an SF value of 2.053 with the highest unit price implication of IDR 52,576,000.00 m3/m